Regeneration of Injured Renal Tubules - Makoto Yoshida; Shigeyoshi Honma (Elsevier, 2014)
Acute kidney injury (AKI), clinically defined by high serum creatinine and low urine flow, has many complicated pathophysiological features including tubular and glomerular injury. Although renal tubules are thought to be constituted by highly differentiated epithelial cells, it is possible to repair injured nephrons by the healing process. Several studies have revealed that AKI, especially AKI caused by ischemia/reperfusion injury or nephrotoxic medication, depends on a number of factors, including activation of transcriptional factors, endothelial injury of peritubular small vessels, immune responses, and inflammatory processes associated with necrosis and apoptosis of renal tubular epithelium. For regeneration of injured tubules, partly dedifferentiated progenitor-like cells fill the injured site and constitute the tubular structure and function, although the source of these cells is still under debate. It is essential to understand the molecular, cellular, and genetic mechanisms of AKI and tubular regeneration for the development of therapies to prevent and treat kidney injury. Keywords:: kidney, regeneration, tubule, acute kidney injury (AKI)